The Agenda- Setting of Television Channels: 2015 Presidential Election Candidates in Prime Time News Bulletins - Kumara, K.W.R.C.P.; Raguram, S. (Trincomalee Campus, Eastern University Sri Lanka, 2016)
The media in Sri Lanka can be broadly placed into two categories- those which are owned and controlled by the State and those which are privately owned and controlled. Many analyses have found that the news media have been unbalanced, especially television channels at the election time, all over the world. However, it seems that the media in Sri Lanka have been used for political promotions. State Media channels directly support the government party candidates. Even though people are expecting balanced news coverage from the media, it is difficult to see that kind of situation in Sri Lankan Society. A scientific research had been needed to study this problem. There are exiguous researches, has occurred via Sri Lankan media to reveal about Agenda Setting in Prime time News bulletins on political campaigns and its balancing, in the role of politics especially during the time of election. It is apparently few of researches have been conducted about the political background of Sri Lanka. Specially there are no researches conducted for Agenda Setting in Prime Time News Bulletins on Political campaign in Sri Lankan media specially related to the 2015 presidential election. Therefore, this has been a significant study for this research. This research study carried out primarily based on the content analysis. The main purpose of this study to investigate the Agenda- Setting of Television Channels: 2015 Presidential Election Candidates in Prime Time News Bulletins. In addition to that to find out the content of political campaigns covered by the prime time news bulletins, whether the television channels covered the political campaigns in a balanced way or not and whether the state media and private media have been biased in supporting or opposing a specific candidate. The study has found out that television channels have been unbalanced, while they covered the political campaigns. Not only that the state media have been biased in supporting to the government candidates than private media in Presidential Election 2015.
Keywords: Agenda Setting; Prime Time; Presidential Election; News Bulletin; Television Channels